1991
DOI: 10.2105/ajph.81.12.1596
|View full text |Cite
|
Sign up to set email alerts
|

HIV instruction, HIV knowledge, and drug injection among high school students in the United States.

Abstract: BACKGROUND. The prevalence of HIV-related behaviors and determinants of these behaviors among adolescents in the United States have not been well studied. METHODS. To determine the prevalence of HIV-related drug behaviors and to assess the effects of HIV-related school-based instruction and HIV knowledge on these behaviors, data were analyzed from a 39-item, self-administered questionnaire completed by a probability sample of all students in grades 9 through 12 in the United States. RESULTS. Usable responses w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
0
2

Year Published

1994
1994
2004
2004

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(12 citation statements)
references
References 16 publications
1
9
0
2
Order By: Relevance
“…Furthermore, the weighted percentages of White, Black, and Hispanic students in both surveys were not unlike the racial and ethnic distribution of 9th through 12th grade students in the United States, suggesting that the samples were representative of the general population of students. 5 Instruction, Knowledge, and Behavior…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, the weighted percentages of White, Black, and Hispanic students in both surveys were not unlike the racial and ethnic distribution of 9th through 12th grade students in the United States, suggesting that the samples were representative of the general population of students. 5 Instruction, Knowledge, and Behavior…”
Section: Methodsmentioning
confidence: 99%
“…Several recent studies have investigated the extent to which adolescents in the United States engage in behaviors that place them at risk for HIV infection. [1][2][3][4][5] Although a few studies have tried to assess changes in these behaviors over time, their findings have been limited. "…”
mentioning
confidence: 99%
“…School-based HIV prevention programs, specifically, have shown to increase HIV/AIDS knowledge, modify attitudes regarding susceptibility to infection, and increase likelihood of using contraception (Brown, Fritz, & Barone, 1989;Kirby, 2002a;Newman, DuRant, Ashworth, & Gaillard, 1993;Siegel, DiClemente, Durbin, Krasnovsky, & Saliba, 1995). One study suggested that knowledge of HIV and school-based instruction may also play a role in maintaining lower levels of IDU behavior among high school students (Holtzman et al, 1991). A previous study found a very strong relationship between sex education classes and condom use on Hispanic adolescent males (Moran & Corley, 1991).…”
Section: School Involvement Adolescents In the Unitedmentioning
confidence: 99%
“…According to TGP (Wingood & DiClemente, 2000), limited access to sex education in schools is a risk factor for HIV, and previous research has indicated that receipt of sex education has a protective effect for HIV and sexual risk behaviors among youth (Armstrong et al, 2009;Kirby, 2002a;Kirby & Lepore, 2007;Holtzman, et al, 1991;Mueller et al, 2008). Kirby, Laris, and Rolleri (2005) found that sex education programs have a positive impact on sexual behavior, including delaying the initial sexual experience and reducing the frequency of sexual activity and number of partners.…”
Section: Sex Educationmentioning
confidence: 99%
See 1 more Smart Citation